Robo-Rabbit Boy, go! - Flintham, Thomas (New York : Branches/Scholastic Inc., 2019)
Super Rabbit Boy's present to Moon Girl releases Queen Spooky and her army of ghosts, and Super Rabbit Boy is taken captive--so it is up to the normally evil King Viking (who does not like the competition of the ghost army) and especially his secret weapon, Robo-Rabbit Boy (switched to "Good" mode) to save Animal Town, release Super Rabbit Boy, and contain the ghosts.
Accelerated Reader
Keywords: Superheroes -- Juvenile fiction; Supervillains -- Juvenile fiction; Robots -- Juvenile fiction; Animals -- Juvenile fiction; Good and evil -- Juvenile fiction; Video games -- Juvenile fiction